Review of the species of Visiana Swinhoe from the Papua New Guinea region (Lepidoptera: Geometridae: Larentiinae) - Schmidt, Olga (Zootaxa, 2013)
The genus Visiana Swinhoe which belongs to the subfamily Larentiinae (Lepidoptera: Geometridae) is widely distributed within the Indo-Australian region. The present study is the first extensive review of historic Visiana specimens from the Papua New Guinea region deposited in the Natural History Museum (London, UK) and Australian National Insect Collection (Canberra, Australia). The species examined are as follows: V. hyperctenista (Prout) from the Bismarck Archipelago, V. vinosa (Warren) from the eastern part of Papua New Guinea, V. ranensis (Prout), stat. nov. from the Moluccas (Indonesia), and four newly described species V. horista, sp. nov. from Bougainville Island, V. grandivinosa sp. nov. from New Britain, V. variovinosa, sp. nov. from the eastern part of Papua New Guinea, and V. morobensis, sp. nov. from the Morobe province. The lectotype is designated for V. hyperctenista. Redescriptions of V. hyperctenista, V. vinosa and V. ranensis are provided, the four new species are described, figures of all seven species are shown. The species V. hyperctenista and V. horista are treated as a sister-group, the diagnostic characters are defined. A checklist of the known Papuan species of the genus Visiana is provided.